Peran Media Sosial dalam Menyebarkan Pesan Nilai-Nilai Aswaja Al-Nahdliyah Bagi Mahasiswa NU Kebumen - Ismiyah, Afridatul; Kurniawan, Benny (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
Humans as social creatures always interact and socialize with other humans who need each other to survive. Current developments are entering the era of digitalization, people are required to live side by side with technology, including social media. The majority of young people spend 8-15 hours on social media every day, whether for personal, group or work purposes. The social media used by generation Z include Facebook, WhatsApp, YouTube, Instagram and TikTok. This research aims to find out and describe the role of social media in embodying the values of Aswaja Al-Nahdliyah. The method used in this research is a descriptive qualitative method, where the results obtained are in the form of explanations regarding the themes raised, not numbers. The research results show that the role of social media in embodying the values of aswaja al-nahdliyah is very good, because the methods used follow current developments such as live broadcasts, podcasts, short videos, motivation and light posts. The conclusion of this research is that the majority of students use social media as a forum for learning about the values of aswaja al-nahdliyah. Students also support the manifestation of Aswaja al-Nahdliyah values through social media